COMBINED TREATMENT OF LANDFILL LEACHATE USING COAGULATION-FLOCCULATION AND ANAEROBIC-AEROBIC BIOFILTER WITH BIOBALL - Sugito, Sugito; Ratnawati, Rhenny; Laba, Vinsensius Fereri (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Piles of waste in landfills can produce leachate that smells bad and contains organic and inorganic materials as well as some pathogenic bacteria. A biofilter is a simple method that can be used to degrade pollutant parameters dissolved in leachate. This research aims to determine the efficiency value of Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Suspended Solid (TSS) concentrations in the leachate of Blandongan Landfill, Pasuruan City. The leachate treatment process uses the coagulation method as pretreatment with aluminum sulfate coagulants (Al2(SO4)3) and Ferric Chloride (FeCl3) followed by biofilter using bioball media. The variables in this research were the differences in the concentration of the coagulant used and the bioball media with a height of 15 cm. The results show that in bioball me-dia the value of reduction efficiency is better in reducing COD levels by 77.73%, BOD by 79.40%, and TSS by 81.48%. This research combines leachate treatment technol-ogy, where the coagulation-flocculation method becomes the pre-treatment of the leachate before continuing with an anaerobic-aerobic biofilter.